A Community Jury on PSA screening: what do well-informed men want the government to do about prostate cancer screening—a qualitative analysis. Issue 4 (30th April 2014) - Rychetnik, Lucie; Doust, Jenny; Thomas, Rae; Gardiner, Robert; MacKenzie, Geraldine; Glasziou, Paul
Abstract : Objective: Cancer screening policies and programmes should take account of public values and concerns. This study sought to determine the priorities, values and concerns of men who were 'fully informed' about the benefits and harms of prostate-specific antigen (PSA) screening; and empirically examine the value of a community jury in eliciting public values on PSA screening. Setting: Community jury was convened on the Gold Coast, Queensland (Australia) to consider PSA screening benefits and harms, and whether government campaigns on PSA screening should be conducted. Participants: 27 men (volunteers) aged 50–70 with no personal history of prostate cancer and willing to attend jury 6–7 April 2013: 12 were randomly allocated to jury (11 attended). Outcome measures: A qualitative analysis was conducted of the jury deliberations (audio-recorded and transcribed) to elicit the jury's views and recommendations. A survey determined the impact of the jury process on participants' individual testing decisions compared with control group. Results: The jury concluded governments should not invest in programmes focused on PSA screening directed at the public because the PSA test did not offer sufficient reassurance or benefit and could raise unnecessary alarm. It recommended an alternative programme to support general practitioners to provide patients with better quality and more consistent information about PSA screening. After the jury, participants were less likely to be tested in the future compared with the controls, but around half said they would still consider doing so. Conclusions: The jury's unanimous verdict about government programmes was notable in the light of their divergent views on whether or not they would be screened themselves in the future. Community juries provide valuable insights into the priorities and concerns of men weighing up the benefits and harms of PSA screening. It will be important to assess the degree to which the findings are generalisable to other settings.